The Role of Customary Leaders in Preserving the Nogigi Tradition in the Kaili Rai Traditional Marriage Ceremony - Andi Talha; Nuraedah Nuraedah; Hasan Hasan; Juraid Juraid (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the role of traditional leaders in preserving the Nogigi tradition within the Kaili Rai traditional wedding ceremony in Tanjung Padang Village, Sirenja District, Donggala Regency. Nogigi is an essential stage containing philosophical, religious, and social values, and is understood as a symbol of self-purification before entering married life. Amid modernization, the continuity of this tradition is closely linked to the role of traditional leaders as guardians of local cultural values. This research applies a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving traditional leaders and community members directly engaged in the practice of Nogigi. The findings indicate that traditional leaders serve as mediators, protectors of tradition, guides of the customary procession, and transmitters of cultural values to the younger generation. Although certain adjustments have occurred in terms of timing, ceremonial equipment, and youth participation due to social change, the core philosophical meaning of Nogigi remains intact. Thus, the sustainability of the Nogigi tradition is maintained through the active involvement of traditional leaders, supported by the community and local government